The influence of feeding behaviour and temperature on the capacity of mosquitoes to transmit malaria - Suh,E; Grossman,M; Waite,J; Dennington,N; Sherrard-Smith,E; Churcher,T; Thomas,M (Nature Ecology and Evolution, 2020)
Insecticide-treated bed nets reduce malaria transmission by limiting contact between mosquito vectors and human hosts when mosquitoes feed during the night. However, malaria vectors can also feed in the early evening and in the morning when people are not protected. Here, we explored how timing of blood feeding interacts with environmental temperature to influence the capacity of Anopheles mosquitoes to transmit the human malaria parasite, Plasmodium falciparum . We found no effect of biting time itself on the proportion of mosquitoes that became infectious (vector competence) at constant temperature. However, when mosquitoes were maintained under more realistic fluctuating temperatures there was a significant increase in competence for mosquitoes feeding in the evening, and a significant reduction in competence for those feeding in the morning, relative to those feeding at midnight. These effects appear to be due to thermal sensitivity of malaria parasites during the initial stages of parasite development within the mosquito, and the fact that mosquitoes feeding in the evening experience cooling temperatures during the night, whereas mosquitoes feeding in the morning quickly experience warming temperatures that are inhibitory to parasite establishment. A transmission dynamics model illustrates that such differences in competence could have important implications for disease endemicity, the extent of transmission that persists in the presence of bed nets, and the epidemiological impact of behavioural resistance. These results indicate the interaction of temperature and feeding behaviour to be a major ecological determinant of the vectorial capacity of malaria mosquitoes.